PERAN KSU DESA KOTA INDONESIA DALAM MEWUJUDKAN KESEJAHTERAAN ANGGOTA PERSPEKTIF MAQASHID SYARIAH - Difa Kholifatus Salam; Ahmad Asrof Fitri; Imam Prawoto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The Multipurpose Cooperative (KSU) plays a strategic role in improving community welfare; however, studies on the social and spiritual dimensions of Islamic cooperative practices remain limited, as previous research has predominantly focused on financial aspects. This study aims to analyze the role of KSU Desa Kota Indonesia in enhancing member welfare through its products and services, as well as to evaluate the realization of Maqashid al-Shariah as the analytical framework. A qualitative field approach was employed through in-depth interviews, observations, and document analysis, with data validation conducted using triangulation techniques. The findings indicate that KSU Desa Kota Indonesia contributes to member welfare by providing access to essential goods, offering low-interest social financing, and enabling income generation through product consignment and SHU/LHU distribution. From the perspective of Maqashid al-Shariah, these practices reflect the fulfillment of hifzh al-din through voluntary and consensual transactions, hifzh al-nafs through the provision of basic needs, hifzh al-nasl through support for family continuity and education, and hifzh al-mal through transparent and trustworthy financial management. Therefore, the study concludes that KSU Desa Kota Indonesia has successfully integrated Maqashid al-Shariah values in realizing comprehensive welfare that encompasses economic, social, and spiritual dimensions. Keywords: Multipurpose Cooperative, Welfare, Maqashid al-Shariah